In-situ growth of Ag/AgBr nanoparticles on a metal organic framework with enhanced visible light photocatalytic performance. (October 2021) - Zhu, Yu; Han, Zhiguo; Zhao, Suya; Zhang, Qiyuan; Shen, Xinru; Lv, Hua; Liu, Jing; Li, Bingdong
Abstract: Recently, the continuous release of antibiotics has resulted in a serious environmental pollution. Tetracycline (TC), one of the most commonly used antibiotics due to the effective antimicrobial effects, is hard to be decomposed in living organisms. Photocatalysis technology, regarded as one of the promising methods has been widely studied to degrade the antibiotics. A series of Ag/AgBr@UiO-66 composites have been constructed to obtain materials with enhanced photocatalytic activities of tetracycline (TC) degradation. The Ag/AgBr@UiO-66 composites were characterized by XRD, SEM, TEM, XPS and BET. Decorated with 25% Ag/AgBr, the composite exhibited the best photocatalytic efficiency thanks to improved adsorption as well as the spatial separation of photogenerated carriers between Ag/AgBr and UiO-66 particles. The photocatalytic mechanism was also studied by free radical capture experiments, revealing that ·O2 is the predominant active specie generated from the electrons on the CB of UiO-66. The PL and photoelectrochemical analyses are the evidence of the fast transfer of electron and hole pairs with inhibiting recombination.